Effectiveness of high-level disinfection by boiling and autoclave sterilization relative to the storage duration of delivery instruments - Sri Lestari Kartikawati; Intan Yusita; Meda Yuliani; Linda Listriyati (Poltekkes Kemenkes Bandung, 2026)
Background: The processing of used delivery instruments is critical in preventing infections in both mothers and newborns. High-level disinfection (HLD) that fails to meet standards can increase infection risks, including those caused by Staphylococcus aureus, which potentially leads to serious complications such as sepsis and maternal mortality. Furthermore, the storage conditions of instruments following HLD can affect their safety for clinical use. Objective: This study aimed to determine the effectiveness of the boiling HLD method and autoclave sterilization on delivery instruments based on storage duration Methods: This comparative quantitative study utilized 42 instrument samples divided into two groups: boiling HLD (100°C for 20 minutes) and autoclave sterilization (121°C at 1 atm for 15 minutes). The instruments were stored in closed sterile containers, then swab-tested on Blood Agar Plate (BAP) media and incubated for 24 hours at 37°C. Data were analyzed using the independent t-test.. Results: Both methods showed 0 CFU on Day 1. On Day 3, microbial growth began to appear (HLD: 16.43 CFU; Autoclave: 13.14 CFU); however, there was no statistically significant difference (p>0.05). By Day 7, the boiling HLD group showed a significant surge in colonies (430.71 CFU) compared to the autoclave group (108.86 CFU), with a highly significant statistical difference (p<0.05). Conclusion: Boiling HLD is effective for sterilizing delivery instruments only if used within a storage duration of ≤3 days. For storage exceeding three days, the autoclave method is significantly more effective, and re-sterilization is recommended to ensure patient safety.